Analisis Pengaruh Kualitas Pelayanan Islam Terhadap Loyalitas Nasabah BPRS Bhakti Sumekar Jember: (Analysis The Effect of Islamic Service Quality on Customer Loyalty BPRS Bhakti Sumekar Jember) - Moh. Adenan; Syara Aulia Febiatillah; Akhmad Munir (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
The purpose of this study is to determine whether compliance, reliability, responsiveness, assurance, empathy, and service facilities have a positive and significant effect on customer loyalty at BPR Syariah Bhakti Sumekar Jember. Quantitative descriptive is used as an approach in this research. The population and sample in this study were all customers of BPRS Bhakti Sumekar Jember, totaling 2083. The sample was taken using simple random sampling and the sample used was 100 respondents. The regression test results show that the variables of compliance, reliability, responsiveness, assurance, empathy, and service facilities partially have a positive and significant effect on customer loyalty of BPR Syariah Bhakti Sumekar Jember. The order of each variable that has the most influence is the service facility variable which has a coefficient of 0.228, then responsiveness 0.197, empathy 0.186, reliability 0.179, assurance 0.157, and the lowest variable is the compliance variable with a regression coefficient of 0.156. Thus, compliance needs to be increased in service delivery, so that if the quality of service provided is getting better, it will make customers loyal.